2014
DOI: 10.1128/aem.00820-14
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Metabolism of N -Acetylglucosamine and Glucosamine by Streptococcus mutans

Abstract: Glucosamine and N-acetylglucosamine are among the most abundant sugars on the planet, and their introduction into the oral cavity via the diet and host secretions, and through bacterial biosynthesis, provides oral biofilm bacteria with a source of carbon, nitrogen, and energy. In this study, we demonstrated that the dental caries pathogen Streptococcus mutans possesses an inducible system for the metabolism of N-acetylglucosamine and glucosamine. These amino sugars are transported by the phosphoenolpyruvate:su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
93
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 89 publications
8
93
1
1
Order By: Relevance
“…2), the expression of nagA and especially nagB was higher in cells growing on GlcN than on glucose, whereas glmS expression was much higher in glucose-grown cells than in GlcN-grown cells, confirming previous results (3,8). However, in the nagR deletion mutant, glmS expression was greatly elevated regardless of the carbohydrate source, nagB expression was actually higher in glucose-grown cells than in GlcNgrown cells of the mutant, and nagA expression was elevated in cells lacking NagR compared with the wild-type strain grown on glucose.…”
Section: Differential Regulation Of Glms and Nagb By Nagr Requires Dresupporting
confidence: 80%
See 3 more Smart Citations
“…2), the expression of nagA and especially nagB was higher in cells growing on GlcN than on glucose, whereas glmS expression was much higher in glucose-grown cells than in GlcN-grown cells, confirming previous results (3,8). However, in the nagR deletion mutant, glmS expression was greatly elevated regardless of the carbohydrate source, nagB expression was actually higher in glucose-grown cells than in GlcNgrown cells of the mutant, and nagA expression was elevated in cells lacking NagR compared with the wild-type strain grown on glucose.…”
Section: Differential Regulation Of Glms and Nagb By Nagr Requires Dresupporting
confidence: 80%
“…In particular, we recently reported that the loss of an apparent homolog of NagR in S. mutans led to the derepression not only of nagA and nagB but also of glmS (3). Moreover, (i) the glmS gene of S. mutans lacks the ribozyme sequences conserved in many Gram-positive bacteria, (ii) dre sites could be identified upstream of the glmS coding sequence, and (iii) purified NagR of S. mutans could bind to the glmS promoter region in vitro (3). Here, we report a more detailed characterization of NagR with respect to its interaction with dre sites and the mechanisms by which it exerts control over the genes needed for the biosynthesis and catabolism of GlcN and GlcNAc.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, all point mutations (in gtfD, ftf, and fruB) in strain MMZ1170 were confirmed by allele-specific PCR followed by sequencing. Lastly, a PCR product containing a manL::Sp replacement marker (conferring spectinomycin resistance) (29) was introduced into strain MMZ1009 via transformation, resulting in strain MMZ1196 (gtfABCD ftf fruAB manL).…”
Section: Methodsmentioning
confidence: 99%